Attenuated airway hyperresponsiveness and mucus secretion in HDM‐exposed Igf1r‐deficient mice. Issue 9 (20th March 2017) - Piñeiro‐Hermida, S.; Gregory, J. A.; López, I. P.; Torrens, R.; Ruíz‐Martínez, C.; Adner, M.; Pichel, J. G.
Abstract: Background: Asthma is a common chronic lung disease characterized by airflow obstruction, airway hyperresponsiveness (AHR), and airway inflammation. IGFs have been reported to play a role in asthma, but little is known about how the insulin‐like growth factor 1 receptor (IGF1R) affects asthma pathobiology. Methods: Female Igf1r‐deficient and control mice were intranasally challenged with house dust mite (HDM) extract or PBS five days per week for four weeks. Lung function measurements, and bronchoalveolar lavage fluid (BALF), serum, and lungs were collected on day 28 for further cellular, histological, and molecular analysis. Results: Following HDM exposure, the control mice responded with a marked AHR and airway inflammation. The Igf1r‐deficient mice exhibited an increased expression of the IGF system and surfactant genes, which were decreased in a similar manner for control and Igf1r‐deficient mice after HDM exposure. On the other hand, the Igf1r‐deficient mice exhibited no AHR, and a selective decrease in blood and BALF eosinophils, lung Il13 levels, collagen, and smooth muscle, as well as a significant depletion of goblet cell metaplasia and mucus secretion markers after HDM exposure. The Igf1r‐deficient mice displayed a distinctly thinner epithelial layer than control mice, but this was not altered by HDM. Conclusions: Herein, we demonstrate by the first time that the Igf1r plays an important role in murine asthma, mediating both AHR and mucus secretion after HDM exposure. Thus, our study identifies IGF1R as a potential therapeutic target, not only for asthma but also for hypersecretory airway diseases.